Gross and histological studies of digestive tract of broilers during postnatal growth and development (Journal of the Bangladesh Agricultural University, 2012)
We studied anatomy and histology of different segments of the digestive tract in postnatal growing broiler chickens  with regard to their location, shape, size and weight. A group of four chickens, each at day 1 (D1), days 14 (D14) and  days 28 (D28), total 12, were killed, their digestive tracts were dissected and described and shape, size and weight of  different segments were recorded. Samples from different segments were prepared and stained with haematoxylin  and eosin staining technique to study the histology under light microscope. The average lengths (cm) and weights  (gm) of esophagus, proventriculus (glandular stomach), gizzard (muscular stomach), small intestine and large  intestine were significantly higher (P